2020
DOI: 10.3389/fgene.2020.01026
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a circRNA-miRNA-mRNA Network Related to Macrophage Infiltration in Hepatocellular Carcinoma

Abstract: Immune cells in the tumor microenvironment play a crucial role in regulating tumor progression. The circular RNA (circRNA) regulatory network involved in immune cell infiltration in hepatocellular carcinoma (HCC) remains largely unknown. In this study, the "estimate the proportion of immune and cancer cells" (EPIC) application is used to evaluate the fractions of immune cells, cancer-associated fibroblasts, and endothelial cells in HCC from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…However, alpha-Fetoprotein bears low specificity owing to its presence in other cancer types ( Schütte et al, 2014 ). Recent genomic works focus on using RNA-related approaches such as mRNA ( Wang et al, 2017 ; Guan et al, 2020 ; Zhou et al, 2020 ) and miRNA signatures ( Liu et al, 2017 ; Bai et al, 2018a ), long non-coding RNAs ( Arun et al, 2018 ; Ma et al, 2020 ) targeted mRNAs for critical genes ( Lin et al, 2016 ), and DNA based approaches such as driver mutations or circulating tumor DNAs ( Yang et al, 2019b ; Cai et al, 2019 ). However, some of the highly predictive biomarkers suffer from requiring invasive procedures or not able to detect the early HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…However, alpha-Fetoprotein bears low specificity owing to its presence in other cancer types ( Schütte et al, 2014 ). Recent genomic works focus on using RNA-related approaches such as mRNA ( Wang et al, 2017 ; Guan et al, 2020 ; Zhou et al, 2020 ) and miRNA signatures ( Liu et al, 2017 ; Bai et al, 2018a ), long non-coding RNAs ( Arun et al, 2018 ; Ma et al, 2020 ) targeted mRNAs for critical genes ( Lin et al, 2016 ), and DNA based approaches such as driver mutations or circulating tumor DNAs ( Yang et al, 2019b ; Cai et al, 2019 ). However, some of the highly predictive biomarkers suffer from requiring invasive procedures or not able to detect the early HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have multiple molecular mechanisms, such as nuclear transcriptional regulators of host genes, RNA-binding protein sequestering agents or miRNA sponges ( Li et al, 2018 ). Thus dysregulated circRNAs have been reported to be involved in a lot of disease such as osteoarthritis, cancer and many ocular disorders ( Zhou et al, 2019 ; Cui et al, 2020 ; Zhou et al, 2020 ; Zou et al, 2020 ; Zheng et al, 2021 ). In our study, we performed high-throughput RNA sequencing of the lacrimal sac samples from chronic dacryocystitis patients and control individuals for the first time and constructed circRNA-mRNA and circRNA-miRNA interaction networks trying to throw light on the pathogenesis of chronic dacryocystitis on RNA level.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the mechanism of action of hsa_circ_0091581 on glioma proliferation, migration, and invasion, we used the results described in the literature that suggested that circRNAs can play a regulatory role by adsorbing miRNAs [30][31][32]. Hsa_circ_0001785 sponges miR-942 to regulate breast cancer progression [33]; hsa_circ_0005556 sponges miR-4270 to facilitate gastric cancer progression [34]; and hsa_circ_0004913 act as a sponge for miR-184 and is thus involved in the progress of hepatocellular carcinoma [35].…”
Section: Discussionmentioning
confidence: 99%